2016
DOI: 10.14254/jems.2017.1-1.3
|View full text |Cite
|
Sign up to set email alerts
|

Challenge of mitigating bank frauds by judicious mix of technology: Experience of a developing country

Abstract: E Ec co on no om mi ic cs s, , MMa an na ag ge em me en nt t a an nd d S Su us st ta ai in na ab bi il li it ty y journal home page: http://jems.sciview.net Bhasin, M. (2016 Abstract: Banks are the engines that drive the operations in the financial sector, money markets and growth of an economy. With the rapidly growing banking industry in India, frauds in banks are also increasing fast, and fraudsters have started using innovative methods. A questionnaire-based survey was conducted in 2013-14 among 345 bank e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 5 publications
(8 reference statements)
2
12
0
1
Order By: Relevance
“…The findings also confirm some empirical studies that found capacity as a major cause of fraud in the financial sector (Baz et al , 2016b, 2016a; Reurink, 2016; Abdullahi and Mansor, 2018; Muhsin et al , 2018b; Sunardi and Amin, 2018). The finding that financial pressure and pressure from related parties can push one to commit fraud substantiates a number of previous studies (Bhasin, 2016; Omar et al , 2016; Maria and Gudono, 2017; Abdullahi and Mansor, 2018; Bonsu et al , 2018; Asmah et al , 2020). Similarly, the positive relationship between rationalisation and occurrence of bank fraud validates empirical literature (Omar et al , 2016; Maria and Gudono, 2017; Abdullahi and Mansor, 2018; Bonsu et al , 2018; Sunardi and Amin, 2018; Asmah et al , 2020).…”
Section: Presentation and Discussion Of Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The findings also confirm some empirical studies that found capacity as a major cause of fraud in the financial sector (Baz et al , 2016b, 2016a; Reurink, 2016; Abdullahi and Mansor, 2018; Muhsin et al , 2018b; Sunardi and Amin, 2018). The finding that financial pressure and pressure from related parties can push one to commit fraud substantiates a number of previous studies (Bhasin, 2016; Omar et al , 2016; Maria and Gudono, 2017; Abdullahi and Mansor, 2018; Bonsu et al , 2018; Asmah et al , 2020). Similarly, the positive relationship between rationalisation and occurrence of bank fraud validates empirical literature (Omar et al , 2016; Maria and Gudono, 2017; Abdullahi and Mansor, 2018; Bonsu et al , 2018; Sunardi and Amin, 2018; Asmah et al , 2020).…”
Section: Presentation and Discussion Of Resultssupporting
confidence: 86%
“…Moreover, poor supervision and improper documentation process provide opportunity to misappropriate the assets, especially when it includes several people that cooperate to conduct those illegal malpractices (Zakaria et al , 2016). Similarly, limited separation of duties, false documentation and inadequate or non-existence of control system accounted for fraud in the Indian banking system (Bhasin, 2016).…”
Section: Theories and Hypothesismentioning
confidence: 99%
“…Pressures can take the form of individuals' condition that encourages unethical actions, namely stress (Piquero et al, 2005), social stress, network and social interaction within the society (Piquero et al, 2005 andBlock &Griffin, 2002). The findings of Bhasin (2016) confirmed that of Said et al (2017) that pressure is a major determinant of fraud. Contrarily, Sunardi & Amin (2018) indicates that pressure had negative effect on the occurrence of financial statement fraud among manufacturing companies listed on the Indonesia Stock Exchange.…”
Section: 1mentioning
confidence: 64%
“…Moreover, poor supervision and improper documentation process provide opportunity to misappropriate the assets, especially when it includes several people that cooperate to conduct those illegal malpractices (Zakaria et al, 2016). Similarly, limited separation of duties, false documentation and inadequate or non-existence of control system accounted for fraud in the Indian banking system (Bhasin, 2016). Based on these arguments, this study proposes the following second hypothesis:…”
Section: H1: Pressure Affects Financial Statement Fraudmentioning
confidence: 97%
“…At first sight, an underlying examination in these cases has uncovered the contribution of not just midlevel workers, but also the seniormost administration as was seen in the recent Syndicate Bank and Indian Bank cases. This raises genuine worry over the adequacy of corporate administration at the most astounding echelons of these banks [7]. Moreover, there has been a rising pattern of non-performing resources (or) assets (NPAs), particularly for the PSBs, in this way seriously affecting their profits.…”
mentioning
confidence: 99%